Piezoelectric composite coating functionalized titanium-based implant material and preparation and application thereof

By constructing piezoelectric barium titanate nanocolumns on the surface of the titanium implant and embedding a hydrogel coating, a functionalized titanium-based implant material is formed by forming a piezoelectric composite coating, which solves the shortcomings of traditional titanium implants in vascularization and bone integration, and achieves the effect of promoting bone regeneration through force-electric coupling signals.

CN119548674AActive Publication Date: 2025-03-04SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411548610.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-04
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

Due to the serious biological inertia, traditional titanium implants limit the process of vascularization and bone integration, and it is difficult to effectively promote bone regeneration and repair.

Method used

The piezoelectric barium titanate nanocolumn is constructed on the surface of the titanium implant through hydrothermal and alkaline heat treatment, and the hydrogel coating is applied in situ on its surface by physical mosaic, forming a piezoelectric composite coating functionalized titanium-based implant material to realize the regulation of force-electric coupling signals.

Benefits of technology

This material is able to bionic the organic-inorganic composite structure of bones, promotes vascularization into bone through mechanical-electrophysical signals, reduces the mechanical modulus of titanium implants, improves the spreading ability of vascular migration, and exhibits excellent coating stability and biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005114474470000011
    Figure HDA0005114474470000011
  • Figure HDA0005114474470000012
    Figure HDA0005114474470000012
  • Figure HDA0005114474470000013
    Figure HDA0005114474470000013
Patent Text Reader

Abstract

The invention discloses a piezoelectric composite coating functionalized titanium-based implant material as well as preparation and application thereof. Piezoelectric barium titanate nano-columns are constructed on the surface of an inert titanium implant through hydrothermal treatment and alkali heat treatment, the material is endowed with piezoelectric responsiveness, then the surfaces of the piezoelectric nano-columns are coated with hydrogel coatings in situ through physical embedding, and the piezoelectric hydrogel coating functionalized titanium-based implant material is constructed. According to the material disclosed by the invention, mechanical-electric coupling signal regulation and control vascularization and osseointegration are realized, and clinical use is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of medical devices, and specifically relates to a piezoelectric composite coating functionalized titanium-based implant material and a preparation and application thereof. Background Art

[0002] In recent years, due to the frequent traffic accidents, the aging population, and the increasing number of patients with high-energy trauma and tumors, the demand for orthopedic implants has increased dramatically. Bone regeneration and repair is divided into four processes. The first stage: hematoma formation, fibrous callus formation, bony callus formation, and bone remodeling; the second stage: hematoma organization, hyperplastic tissue bridging, and then fibrosis occurs to form fibrous callus. This stage mainly involves vascularization; the third stage: osteoblasts produce new bone to gradually replace the fibrous callus, and begin to form bone-like tissue. Calcium salts are deposited to form bony callus. This stage mainly involves bone integration. Clinical orthopedic implants such as titanium and its alloys are usually used for load-bearing bone replacement, spinal fusion, and bone fixation devices due to their excellent mechanical properties and biocompatibility. However, traditional titanium implants are severely limited in vascularization and bone integration due to their biological inertness.

[0003] Bioelectricity is an important component of the regenerative microenvironment and a fundamental mechanism for tissue response to external stimuli and regulation of cell fate. Endogenous piezoelectricity is widely believed to be closely related to the growth and remodeling of bone tissue, and the intrinsic piezoelectric properties play a key role in bone remodeling and repair. In addition, the viscoelastic matrix is ​​an important biophysical cue that regulates the biological behavior of human bone marrow mesenchymal stem cells through mechanical transduction consistent with cell-matrix interactions. Mechanical signal transduction affects vascular migration and bone tissue regeneration and repair during bone healing through multiple mechanisms.

[0004] Therefore, it is urgent to develop an implant material that can promote vascularization and bone integration through electromechanical coupling signals to meet clinical use. Summary of the invention

[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a piezoelectric composite coating functionalized titanium-based implant material.

[0006] In order to achieve the regulation of bone integration by piezoelectric properties, the present invention constructs piezoelectric barium titanate nanocolumns on the surface of inert titanium implants through hydrothermal and alkali heat treatment to give the material piezoelectric responsiveness; in order to achieve the regulation of vascularization and bone integration by mechanoelectric coupling signals, a hydrogel coating is in situ coated on the surface of the piezoelectric nanocolumns through physical intercalation to construct a piezoelectric composite coating functionalized titanium-based implant material.

[0007] Another object of the present invention is to provide a piezoelectric composite coating functionalized titanium-based implant material prepared by the above preparation method. Natural bone is a composite material similar to polymer ceramics, consisting of about 65% inorganic components and 25-30% organic components. From the perspective of bionic bone, the piezoelectric composite coating functionalized titanium-based implant material constructed by the present invention promotes vascularization and osteogenesis through electromechanical coupling.

[0008] Another object of the present invention is to provide an application of the above-mentioned piezoelectric composite coating functionalized titanium-based implant material.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing a piezoelectric composite coating functionalized titanium-based implant material comprises the following steps:

[0011] (1) placing the titanium implant in an alkaline solution for alkaline thermal reaction, and then placing the titanium implant in a barium hydroxide solution for hydrothermal reaction to obtain a barium titanate nanostructure implant;

[0012] (2) adding methacrylic anhydride dropwise to a phosphate buffer solution containing gelatin to react, and after the reaction is completed, centrifuging, dialysis, and freeze-drying to obtain a GelMA hydrogel;

[0013] (3) The GelMA hydrogel is dissolved in a phosphate buffer solution containing a photoinitiator, and the resulting mixed solution is spin-coated onto the surface of the barium titanate nanostructure implant and photocured to obtain a piezoelectric hydrogel coating functionalized titanium-based implant material.

[0014] Preferably, the titanium implant in step (1) needs to be pretreated, and the pretreatment comprises: ultrasonic cleaning, acid washing, and drying the titanium implant to obtain a pretreated titanium-based substrate.

[0015] More preferably, the ultrasonic cleaning refers to immersing the titanium implant in acetone, anhydrous ethanol, and deionized water in sequence and performing ultrasonic cleaning for 10 to 20 minutes respectively.

[0016] More preferably, the pickling is to first add nitric acid and hydrofluoric acid to deionized water in sequence to prepare an acid solution, stir it evenly, and then add it into the titanium implant for pickling.

[0017] More preferably, the drying temperature is 40-80° C. and the drying time is 0.5-2 h.

[0018] Preferably, the alkaline solution in step (1) is a sodium hydroxide solution; the concentration of the alkaline solution is 6 to 10 mol / L; more preferably 8 mol / L.

[0019] Preferably, the temperature of the alkali thermal reaction in step (1) is 90-120° C. and the time is 18-24 h; more preferably, the temperature of the alkali thermal reaction is 100° C. and the time is 24 h.

[0020] Preferably, the concentration of the barium hydroxide solution in step (1) is 0.03-0.08 mol / L; more preferably 0.05 mol / L.

[0021] Preferably, the temperature of the hydrothermal reaction in step (1) is 180-210° C., and the time is 6-10 h; more preferably, the temperature of the hydrothermal reaction is 210° C., and the time is 8 h.

[0022] Preferably, the mass ratio of the gelatin in step (2) to the volume of the phosphate buffer is 0.05-0.2 g:1 ml; more preferably 0.1 g:1 ml; the mass ratio of the methacrylic anhydride to the gelatin is 0.3-1.0:1; more preferably 0.94:1.

[0023] Preferably, the pH of the phosphate buffer in steps (2) and (3) is 6 to 8; more preferably 7.4.

[0024] Preferably, the reaction temperature in step (2) is 50-60°C and the reaction time is 2-4 hours; more preferably, the reaction temperature is 50°C and the reaction time is 3 hours.

[0025] Preferably, in step (2), phosphate buffer is added to the reaction system to terminate the reaction.

[0026] Preferably, the centrifugal speed in step (2) is 5000-10000 rpm, and the time is 3-5 min.

[0027] Preferably, the dialysis time in step (2) is 3 to 7 days.

[0028] Preferably, in the phosphate buffer containing the photoinitiator in step (3), the mass concentration of the photoinitiator is 0.2-0.3%, and more preferably 0.25%.

[0029] Preferably, the photoinitiator in step (3) is at least one of LAP and photoinitiator 2959.

[0030] Preferably, the volume ratio of the mass of the GelMA hydrogel in step (3) to the phosphate buffer containing the photoinitiator is 0.5-2 g:10 ml; more preferably 1 g:10 ml.

[0031] Preferably, the spin coating speed in step (3) is 500 to 3000 r / min, and the time is 10 to 60 s.

[0032] Preferably, the ratio of the volume of the mixed solution in step (3) to the area of ​​the barium titanate nanostructure implant is 30-130 μL: 1 cm 2 ; More preferably 38μL: 1cm 2 .

[0033] Preferably, the light curing time in step (3) is 30 to 300 seconds, and the curing light source is ultraviolet light.

[0034] The preparation method mentioned above produces a piezoelectric composite coating functionalized titanium-based implant material.

[0035] The above-mentioned piezoelectric composite coating functionalized titanium-based implant material is used in the preparation of medical devices.

[0036] Preferably, the invention is used in the preparation of electromechanical coupling hydrogel modified titanium implant material.

[0037] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0038] (1) The piezoelectric hydrogel coating functionalized titanium-based implant material prepared by the present invention can mimic the organic-inorganic composite structure of bones and promote vascularization and osteogenesis through mechanical-electrical biophysical signals.

[0039] (2) The hydrogel coating prepared by the present invention effectively reduces the mechanical modulus of the titanium implant and facilitates the migration and spreading of blood vessels.

[0040] (3) The hydrogel prepared by the present invention and the piezoelectric nanocolumn titanium-based implant material are physically interlocked through a spin coating process, showing excellent coating stability, which is beneficial to practical clinical applications.

[0041] (4) The present invention proposes a method for preparing an organic-inorganic coating implant material with a force-electric coupling signal, which has a simple process, low cost, short cycle, and is suitable for industrial production.

[0042] (5) The spin coating process of the present invention helps to form a uniform microstructure without obvious particle aggregation, and the electromechanical signal of the thin film material is stable, indicating the reliability of the film forming process. In addition, the thin film prepared by the spin coating process has a smooth surface and high bonding strength, which is crucial to improving the durability and performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 These are scanning electron microscope (SEM) images of the materials of Example 1, where (A) is GelMA hydrogel (BTO), (B) is barium titanate (BTO) array, and (C) is GelMA / BTO.

[0044] Figure 2These are subjective morphology pictures of Example 1 and Comparative Example 1, where A is a Ti sheet, B is a flat Ti-BTO, C is an array Ti-BTO, D is Ti-GelMA, E is a flat Ti-BTO-GelMA, and F is an array Ti-BTO-GelMA. The microscopic morphology proves that only the array BTO surface can grow a uniform hydrogel coating.

[0045] Figure 3 These are scanning electron microscope (SEM) images of Example 1 and Comparative Example 2, A is Ti-GelMA, B is Ti-BTO-GelMA prepared by dipping method, and C is Ti-BTO-GelMA prepared by spin coating. SEM shows that only the surface of the array BTO can form a hydrogel coating with uniform thickness.

[0046] Figure 4 This is the NMR spectrum of GelMA in Example 1.

[0047] Figure 5 This is the XRD pattern of the barium titanate array in Example 1.

[0048] Figure 6 Infrared spectra of GelMA, Ti-BTO, and Ti-BTO-GelMA.

[0049] Figure 7 is the elastic modulus of Ti, Ti-BTO and Ti-BTO-GelMA.

[0050] Figure 8 This is the electrical signal generated by the electromechanical coupling of the hydrogel coating in Example 1.

[0051] Fig. 9 Live-dead staining of Example 1 proves the excellent biocompatibility of the material.

[0052] Fig.10 The staining of the cytoskeleton and the quantitative characterization of the skeleton spreading area in Example 1 prove that the material is conducive to the growth and spreading of cells. DETAILED DESCRIPTION

[0053] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0054] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0055] Example 1

[0056] A method for preparing a piezoelectric composite coating functionalized titanium-based implant material comprises the following steps:

[0057] (1) Pretreatment of titanium substrate: The titanium implant was sequentially immersed in acetone, anhydrous ethanol, and deionized water for ultrasonic cleaning for 15 min, and then 2.61 ml of nitric acid and 1.831 ml of hydrofluoric acid were added dropwise to 400 ml of deionized water. The titanium implant was immersed in the deionized water for 15 min and stirred. The titanium implant was taken out and immersed in deionized water for ultrasonic cleaning for 5 min. The implant was placed in a thermostat set at 60°C and dried for 1 h to obtain the pretreated titanium implant.

[0058] (2) Preparation of inorganic piezoelectric barium titanate nanocolumn materials on titanium surfaces: The pretreated titanium implant was placed in 60 mL, 8 mol / L sodium hydroxide solution for alkaline thermal reaction, the temperature was set to 100°C, the reaction time was 24 hours, and after the reaction, a sodium titanate nanostructure implant was obtained. The sodium titanate nanostructure implant was placed in 60 mL, 0.05 mol / L barium hydroxide solution for hydrothermal reaction, the temperature was set to 210°C, the reaction time was 8 hours, and after the reaction, a barium titanate nanostructure implant was obtained.

[0059] (3) Preparation of methacrylated gelatin: 10 g of gelatin was placed in 100 ml of PBS solution with a pH of 7.4, and stirred magnetically at 60°C for 30 min. 9 ml of methacrylic anhydride was added dropwise with a syringe, and stirred at 50°C for 3 h. 400 ml of PBS solution with a pH of 7.4 was added to terminate the reaction for 30 min. The solution was poured into a centrifuge tube and incubated at 5000 rpm for 3-5 min. The supernatant was taken and placed in a dialysis bag. After dialysis for 5 days, the supernatant was freeze-dried at -60°C for 3 days in a freeze dryer to obtain GelMA hydrogel.

[0060] (4) Preparation of piezoelectric hydrogel coating functionalized titanium-based implant material: Take 0.0025g of photoinitiator LAP and dissolve it in 1ml of PBS solution with pH = 7.4, take 0.1g of GelMA hydrogel and dissolve it in the above solution to obtain GelMA prepolymer solution. Place a 1cm diameter round sheet of barium titanate nanostructure implant on a gelator, set the speed to 1000r / min, and the time to 30s. Use a pipette to transfer 30μL of GelMA prepolymer solution for spin coating. After the spin coating is completed, irradiate with UV light for 60s to obtain a piezoelectric hydrogel coating functionalized titanium-based implant material.

[0061] Relevant characterization of the piezoelectric hydrogel coating functionalized titanium-based implant material prepared in Example 1:

[0062] like Figure 1 As shown in the figure, the barium titanate nanostructures are evenly distributed on the surface, while the hydrogel coating is evenly dispersed on the surface of the piezoelectric array, so the hydrogel coating and piezoelectric nanopillars are observed on the surface of the titanium implant. Figure 2 , Figure 3As shown, compared with Example 1, Comparative Examples 1 and 2, it is proved that Comparative Examples 1 and 2 cannot prepare uniform hydrogel coatings. Figure 4 As shown, the characteristic peak of GelMA was observed at ppm = 5.7, proving the successful preparation of the hydrogel. Figure 5 As shown in Figure 1, Ti, O, and Bi elements can be observed in titanium implants. Figure 6 As shown in Figure 2, infrared spectroscopy confirmed the successful preparation of Ti-BTO-GelMA. Figure 7 As shown in Figure 2, the viscoelastic hydrogel coating effectively reduces the mechanical strength of the titanium implant. The electrical signal generated by the electromechanical coupling of the hydrogel coating is shown in Figure 2. Figure 8 As shown. Fig. 9 As shown in Figure 2, live-dead staining demonstrated the excellent biocompatibility of the material. Fig.10 As shown, piezoelectric hydrogel-coated titanium-based implants facilitate the expansion of the skeleton.

[0063] Comparative Example 1

[0064] (1) Pretreatment of titanium substrate: The titanium implant was sequentially immersed in acetone, anhydrous ethanol, and deionized water for ultrasonic cleaning for 15 min, and then 2.61 ml of nitric acid and 1.831 ml of hydrofluoric acid were added dropwise to 400 ml of deionized water. The titanium implant was immersed in the deionized water for 15 min and stirred. The titanium implant was taken out and immersed in deionized water for ultrasonic cleaning for 5 min. The titanium implant was placed in a thermostat set at 60°C and dried for 1 h to obtain the pretreated titanium implant.

[0065] (2) Preparation of inorganic piezoelectric barium titanate nanocolumn materials on titanium surfaces: The pretreated titanium implant was placed in 60 mL, 8 mol / L sodium hydroxide solution for alkaline thermal reaction, the temperature was set to 100°C, the reaction time was 24 hours, and after the reaction, a sodium titanate nanostructure implant was obtained. The sodium titanate nanostructure implant was placed in 60 mL, 0.05 mol / L barium hydroxide solution for hydrothermal reaction, the temperature was set to 210°C, the reaction time was 8 hours, and after the reaction, a barium titanate nanostructure implant was obtained.

[0066] (3) Preparation of methacrylated gelatin: 10 g of gelatin was placed in 100 ml of PBS solution with a pH of 7.4, and stirred magnetically at 60°C for 30 min. 9 ml of methacrylic anhydride was added dropwise with a syringe, and stirred at 50°C for 3 h. 400 ml of PBS solution with a pH of 7.4 was added, and the reaction was terminated for 30 min. The solution was poured into a centrifuge tube and incubated at 5000 rpm for 3-5 min. The supernatant was taken and placed in a dialysis bag. After dialysis for 5 days, it was freeze-dried in a freeze dryer for 3 days to obtain GelMA hydrogel.

[0067] (4) Preparation of piezoelectric hydrogel coating functionalized titanium-based implant material: 0.0025 g of photoinitiator LAP was dissolved in 1 ml of PBS solution with pH = 7.4, and 0.1 g of GelMA hydrogel was dissolved in the above solution to obtain GelMA prepolymer solution. A 1 cm diameter round sheet of barium titanate nanostructure implant was immersed in 30 μL of GelMA prepolymer solution for 30 seconds and then irradiated with UV light for 60 seconds.

[0068] Comparative Example 2

[0069] (1) Pretreatment of titanium substrate: The titanium implant was sequentially immersed in acetone, anhydrous ethanol, and deionized water for ultrasonic cleaning for 15 min, and then 2.61 ml of nitric acid and 1.831 ml of hydrofluoric acid were added dropwise to 400 ml of deionized water. The titanium implant was immersed in the deionized water for 15 min and stirred. The titanium implant was taken out and immersed in deionized water for ultrasonic cleaning for 5 min. The titanium implant was placed in a thermostat set at 60°C and dried for 1 h to obtain the pretreated titanium implant.

[0070] (2) Preparation of titanium-based barium titanate material with flat surface: The pretreated titanium implant was placed in a 60 mL, 0.1 mol / L barium hydroxide and 0.1 mol / L KOH mixed solution for alkaline thermal reaction. The temperature was set to 180°C and the reaction time was 8 h. After the reaction was completed, a flat barium titanate implant was obtained.

[0071] (3) Preparation of methacrylated gelatin: 10 g of gelatin was placed in 100 ml of PBS solution with a pH of 7.4, and stirred magnetically at 60°C for 30 min. 9 ml of methacrylic anhydride was added dropwise with a syringe, and stirred at 50°C for 3 h. 400 ml of PBS solution with a pH of 7.4 was added to terminate the reaction for 30 min. The solution was poured into a centrifuge tube and incubated at 5000 rpm for 3-5 min. The supernatant was taken and placed in a dialysis bag. After dialysis for 5 days, the supernatant was freeze-dried at -60°C for 3 days in a freeze dryer to obtain GelMA hydrogel.

[0072] (4) Preparation of piezoelectric hydrogel coating functionalized titanium-based implant material: Take 0.0025g of photoinitiator LAP and dissolve it in 1ml of PBS solution with pH = 7.4, take 0.1g of GelMA hydrogel and dissolve it in the above solution to obtain GelMA prepolymer solution. Place a flat barium titanate implant with a diameter of 1cm in a round sheet on a gelator, set the speed to 1000r / min, and the time to 30s. Use a pipette to transfer 30μL of GelMA prepolymer solution for spin coating. After the spin coating is completed, irradiate with UV light for 60s.

[0073] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a piezoelectric composite coating functionalized titanium-based implant material, characterized in that: The following steps are involved: (1) placing the titanium implant in an alkaline solution for alkaline thermal reaction, and then placing the titanium implant in a barium hydroxide solution for hydrothermal reaction to obtain a barium titanate nanostructure implant; (2) adding methacrylic anhydride dropwise to a phosphate buffer solution containing gelatin to react, and after the reaction is completed, centrifuging, dialysis, and freeze-drying to obtain a GelMA hydrogel; (3) The GelMA hydrogel is dissolved in a phosphate buffer solution containing a photoinitiator, and the resulting mixed solution is spin-coated onto the surface of the barium titanate nanostructure implant and photocured to obtain a piezoelectric composite coating functionalized titanium-based implant material.

2. The method for preparing a piezoelectric composite coating functionalized titanium-based implant material according to claim 1, characterized in that: In step (3), the volume ratio of the mass of the GelMA hydrogel to the phosphate buffer containing the photoinitiator is 0.5-2 g:10 ml; The spin coating speed in step (3) is 500 to 3000 r / min, and the time is 10 to 60 s; The ratio of the volume of the mixed solution in step (3) to the area of ​​the barium titanate nanostructure implant is 30-130 μL: 1 cm 2 .

3. The method for preparing a piezoelectric composite coating functionalized titanium-based implant material according to claim 1, characterized in that: In the phosphate buffer containing the photoinitiator in step (3), the mass concentration of the photoinitiator is 0.2-0.3%; The photoinitiator in step (3) is at least one of LAP and photoinitiator 2959; The light curing time in step (3) is 30 to 300 seconds, and the curing light source is ultraviolet light.

4. The method for preparing a piezoelectric composite coating functionalized titanium-based implant material according to claim 1, characterized in that: The alkaline solution in step (1) is a sodium hydroxide solution; the concentration of the alkaline solution is 6 to 10 mol / L; The temperature of the alkaline thermal reaction in step (1) is 90 to 120° C. and the time is 18 to 24 hours; The concentration of the barium hydroxide solution in step (1) is 0.03-0.08 mol / L; The temperature of the hydrothermal reaction in step (1) is 180-210° C. and the time is 6-10 hours.

5. The method for preparing a piezoelectric composite coating functionalized titanium-based implant material according to claim 1, characterized in that: In step (2), the mass ratio of gelatin to phosphate buffer is 0.05-0.2 g:1 ml; the mass ratio of methacrylic anhydride to gelatin is 0.3-1.0:1; The reaction temperature in step (2) is 50-60°C and the reaction time is 2-4h; The pH of the phosphate buffer in steps (2) and (3) is 6-8.

6. The method for preparing a piezoelectric composite coating functionalized titanium-based implant material according to claim 1, characterized in that: The volume ratio of the mass of the GelMA hydrogel in step (3) to the phosphate buffer containing the photoinitiator is 1 g:10 ml; The ratio of the volume of the mixed solution in step (3) to the area of ​​the barium titanate nanostructure implant is 38 μL: 1 cm 2 ; The spin coating speed in step (3) is 1000 r / min and the time is 30 s.

7. The method for preparing a piezoelectric composite coating functionalized titanium-based implant material according to claim 1, characterized in that: The concentration of the alkaline solution in step (1) is 8 mol / L; The temperature of the alkaline thermal reaction in step (1) is 100° C. and the time is 24 hours; The concentration of the barium hydroxide solution in step (1) is 0.05 mol / L; The temperature of the hydrothermal reaction in step (1) is 210° C. and the time is 8 h; In step (2), the mass ratio of gelatin to phosphate buffer is 0.1 g:1 ml; the mass ratio of methacrylic anhydride to gelatin is 0.94:1; The pH of the phosphate buffer in steps (2) and (3) is 7.4; The reaction temperature in step (2) is 50° C. and the reaction time is 3 h.

8. The method for preparing a piezoelectric composite coating functionalized titanium-based implant material according to claim 1, characterized in that: The titanium implant of step (1) needs to be pretreated, and the pretreatment comprises: ultrasonically cleaning the titanium implant and drying it to obtain a pretreated titanium-based substrate; The ultrasonic cleaning refers to immersing the titanium implant in acetone, anhydrous ethanol, and deionized water in sequence and performing ultrasonic cleaning for 10 to 20 minutes respectively; The pickling refers to first adding nitric acid and hydrofluoric acid to deionized water in sequence to prepare an acid solution, stirring it evenly and then adding it to the titanium implant for pickling.

9. A piezoelectric composite coating functionalized titanium-based implant material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the piezoelectric composite coating functionalized titanium-based implant material according to claim 9 in the preparation of medical devices.

Citation Information

Patent Citations

  • Preparation method for biological piezoelectric antibacterial coating on surface of medical titanium alloy

    CN113502524A

  • BaTiO3 composite piezoelectric hydrogel as well as preparation method and application thereof

    CN117883632A

  • Barium titanate-hydroxyapatite coating based on titanium substrate and preparation method

    CN118086902A